Spray-dried assembly of 3D N, P-Co-doped graphene microspheres embedded with core–shell CoP/MoP@C nanoparticles for enhanced lithium-ion storage. Issue 13 (17th March 2021) - Muhammad, Ishaq; Jabeen, Maher; Wang, Peiran; He, Yu-Shi; Liao, Xiao-Zhen; Ma, Zi-Feng
Abstract : A novel synthesis route was developed for the fabrication of 3D N, P dual-atom doped graphene (G-NP) microspheres embedded with core–shell CoP@C and MoP@C nanoparticles (CoP@C⊂G-NP and MoP@C⊂G-NP) as anode materials for lithium-ion batteries. Abstract : The advancement of novel synthetic approaches for micro/nanostructural manipulation of transition metal phosphide (TMP) materials with precisely controlled engineering is crucial to realize their practical use in batteries. Here, we develop a novel spray-drying strategy to construct three-dimensional (3D) N, P co-doped graphene (G-NP) microspheres embedded with core–shell CoP@C and MoP@C nanoparticles (CoP@C⊂G-NP, MoP@⊂G-NP). This intentional design shows a close correlation between the microstructural G-NP and chemistry of the core–shell CoP@C/MoP@C nanoparticle system that contributes towards their anode performance in lithium-ion batteries (LIBs). The obtained structure features a conformal porous G-NP framework prepared via the co-doping of heteroatoms (N, P) that features a 3D conductive highway that allows rapid ion and electron passage and maintains the overall structural integrity of the material. The interior carbon shell can efficiently restrain volume evolution and prevent CoP/MoP nanoparticle aggregation, providing excellent mechanical stability. As a result, the CoP@C⊂G-NP and MoP@⊂G-NP composites deliver high specific capacities of 823.6 and 602.9 mA h g −1 at a current density of 0.1 A g −1 and exhibit excellent cycling stabilities of 438 and 301 mA h g −1 after 500 and 800 cycles at 1 A g −1 . The present work details a novel approach to fabricate core–shell TMPs@C⊂G-NP-based electrode materials for use in next-generation LIBs and can be expanded to other potential energy storage applications.